2017
DOI: 10.1155/2017/1402320
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug Resistant Pseudomonas Mycotic Pseudoaneurysm following Cardiac Transplant Bridged by Ventricular Assistant Device

Abstract: Mycotic pseudoaneurysm of aorta following cardiac surgery is rare but is highly fatal if it is unrecognized and untreated. Here, we report a case of a 45-year-old male patient who presented with rapidly progressive multiple pseudoaneurysms of the ascending aorta infected with multidrug resistant (MDR) Pseudomonas aeruginosa at 5 weeks after cardiac transplantation, on a background of prior bridging therapy with left ventricular assistant device (LVAD). The patient was successfully treated with the newer cephal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Furthermore, this review identified 30 publications reporting a total of 364 immunocompromised patients [ 22 , 26 , 27 , 30 , 34 , 37 39 , 41 , 43 , 48 , 49 , 51 , 53 , 59 61 , 63 , 68 , 73 , 79 , 83 – 86 , 90 , 91 , 96 – 98 ]. Immunocompromised patients include those with a history of organ transplant, disease suppressing immunity (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this review identified 30 publications reporting a total of 364 immunocompromised patients [ 22 , 26 , 27 , 30 , 34 , 37 39 , 41 , 43 , 48 , 49 , 51 , 53 , 59 61 , 63 , 68 , 73 , 79 , 83 – 86 , 90 , 91 , 96 – 98 ]. Immunocompromised patients include those with a history of organ transplant, disease suppressing immunity (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, 15 single-patient case reports reported C/T durations exceeding the maximum label dose, with 12 reporting a duration of > 28 days, and three reporting a duration of > 42 days. All three that reported a duration of > 42 days administered 8-week courses of C/T [ 56 , 63 , 67 ]. Two patients received C/T for XDR P. aeruginosa osteomyelitis [ 56 , 67 ], and one received C/T for MDR P. aeruginosa mycotic pseudoaneurysm [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…4 ). Resected specimen of ascending aortic pseudoaneurysms of heart transplant patients frequently grows Staphylococcus aureus [ 4 17 ], P. aeruginosa [ 7 , 14 , 18 23 ] or Candida species, [ 7 , 14 , 21 , 24 – 29 ] but other gram-positive [ 7 , 14 , 30 , 31 ] or gram-negative [ 14 , 32 ] bacteria and Aspergillus fumigatus [ 33 – 35 ] are also reported as potential pathogens.
Fig.
…”
Section: Discussionmentioning
confidence: 99%
“…The following predisposing factors for aortic wall infection and formation of mycotic pseudoaneurysm are documented in literature: intrathoracic infection (50%) [ 6 – 8 , 10 , 14 16 , 24 , 25 , 30 , 33 , 35 , 36 ], pneumonia or bronchitis (20%) [ 4 , 13 , 17 , 19 , 21 , 25 , 26 ], heart–lung transplantation (17.5%) [ 4 , 14 , 15 , 19 , 25 ], reoperation due to bleeding (15%), [ 4 , 8 , 13 , 31 ] diabetes mellitus (15%), [ 7 , 12 , 15 , 31 , 35 , 37 ] infection of a previous ventricular assist device (12.5%) [ 9 , 14 , 22 , 23 ], transmission of microorganisms from the donor (7.5%) [ 8 , 25 ], acute cholecystitis (5%) [ 28 , 33 ], urinary tract infection (5%) [ 18 , 31 ], other septicaemia (5%), [ 17 , 21 ] pacemaker endocarditis (2.5%), [ 13 ] skin disruption (2.5%), [ 29 ] heart–lung retransplantation (2.5%) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another recent study, C/T was successful in treating 15/21 patients with various MDR P. aeruginosa infections (71%), although it should be noted that resistance to C/T conferred by de novo mutations occurred in 14% of cases (3/21) [43]. Regarding case reports and small case series, they also mainly reported on the successful off-label use of C/T for treating infections due MDR P. aeruginosa (mostly pneumonia, bloodstream infections, osteomyelitis, and acute pulmonary exacerbation of cystic fibrosis) [54,[93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112]. More reports will come in the near future, that remain critical to enrich our knowledge about the effectiveness of C/T for all these indications.…”
Section: C/t In Mdr-p Aeruginosa In Many Countries Approximatelymentioning
confidence: 99%